2021
DOI: 10.1177/14713012211002030
|View full text |Cite
|
Sign up to set email alerts
|

Familiarity and participation outside home for persons living with dementia

Abstract: Familiarity is important for persons living with dementia who participate outside home. When familiarity is challenged, such participation may be difficult. This ethnographic study clarifies how familiarity is experienced by persons with dementia in performing activities and visiting places, and how familiarity contributes to maintaining participation outside home. Nine participants were interviewed in their home and while visiting familiar places. Data were content analysed using a constant comparative method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…Participants wanted to focus on activities they had always done for as long as possible, and discover new activities [ 69 , 70 , 78 , 104 , 116 , 119 , 122 ]. A wide range of leisure activities are mentioned: watching TV [ 88 , 89 , 90 , 97 , 101 ], reading books [ 78 , 88 , 102 , 121 ], gardening [ 101 , 102 ], creative and cultural activities such as painting and singing in a choir [ 67 , 70 , 77 , 90 , 91 , 99 , 102 , 122 ] and physical activities such as walking and doing exercises [ 66 , 67 , 68 , 72 , 74 , 83 , 93 , 95 , 96 , 101 , 102 , 104 , 113 , 116 , 120 , 122 ]. In five studies participants stressed that they liked to learn new things, either individually or with other people with dementia, such as learning to write, knit or use a tablet to play online games [ 81 , 101 , 102 , 116 , 122 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Participants wanted to focus on activities they had always done for as long as possible, and discover new activities [ 69 , 70 , 78 , 104 , 116 , 119 , 122 ]. A wide range of leisure activities are mentioned: watching TV [ 88 , 89 , 90 , 97 , 101 ], reading books [ 78 , 88 , 102 , 121 ], gardening [ 101 , 102 ], creative and cultural activities such as painting and singing in a choir [ 67 , 70 , 77 , 90 , 91 , 99 , 102 , 122 ] and physical activities such as walking and doing exercises [ 66 , 67 , 68 , 72 , 74 , 83 , 93 , 95 , 96 , 101 , 102 , 104 , 113 , 116 , 120 , 122 ]. In five studies participants stressed that they liked to learn new things, either individually or with other people with dementia, such as learning to write, knit or use a tablet to play online games [ 81 , 101 , 102 , 116 , 122 ].…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, in 15 studies people reported that they had to reconcile themselves with downsizing or giving up hobbies and activities, for example because of difficulties in concentration, memory problems or physical complaints [ 66 , 68 , 72 , 80 , 81 , 83 , 88 , 91 , 93 , 98 , 102 , 114 , 116 , 122 , 123 ]. Other specific hindrances described are the feeling of being excluded [ 123 ], the absence of group activities [ 83 , 96 ], or difficulty to pay fees for activities [ 95 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Modifications and adaptations to built, social and supportive service environmental factors can have a wide-ranging effect on out-of-home participation for persons living with dementia and contribute to create Dementia-Friendly Communities ( Gaber, 2021 ). Besides the neighbourhood built environment, other aspects, such as geographical, demographic, social and organisational aspects, city planning and healthcare authorities may also contribute to how a person experiences out-of-home participation in different activities and places ( Gaber, 2021 ; Margot-Cattin, 2021 ). This operationalisation of out-of-home participation in the ACT-OUT survey allows systematic examination of the topic, thereby shedding light on commonalities as well as differences among environments.…”
Section: Background and Objectivesmentioning
confidence: 99%
“…Diverse factors can exert an influence on the social participation of older adults with dementia, such as cognitive and physical capacity (Kolanowski et al., 2015), family relationships (Margot‐Cattin et al., 2021), communication difficulty due to the different stages of the disease (Murphy & Oliver, 2013), the social support network, such as support from caregivers (Gräske et al., 2015), social stigma (Rewerska‐Juśko & Konrad Rejdak, 2020) and environmental factors (Cohen‐Mansfield et al., 2012). Moreover, such individuals are more likely to abandon social activities with the progression of the symptoms (Chaudhury et al., 2021).…”
Section: Introductionmentioning
confidence: 99%